Pemberdayaan Teaching Factory Nutrition Care Center Dalam Meningkatkan Pelayanan Gizi Kepada Masyarakat - mudiono , Demiawan rachmatta putro; Muflihatin, Indah; Wicaksono, Andri Permana; Wahyono, Nanang Dwi; Ayyubi, Waridad Umais Al; mudiono , demiawan (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2024)
Health is one of the sectors that has rapidly advanced through the application of information and communication technology (ICT) under the concept of e-Health. Nutrition services at the Teaching Factory Nutrition Care Center (TeFa NCC) are still conducted manually, requiring technological innovations to enhance efficiency and accessibility. This community service aims to digitalize nutrition services to facilitate public access to information and support staff operations more effectively. The method involves a participatory approach with three main steps: application development, socialization, and monitoring and evaluation to improve the quality of nutrition services and user satisfaction. The development of the Android-based E-Stagi application has proven successful in increasing service efficiency, with 34% of users finding the application very easy to operate. Monitoring results also indicate that the application simplifies data management for staff and provides easier access to nutrition information for the public compared to traditional methods. Despite technical challenges and user unfamiliarity, further training and application updates are necessary to optimize its utilization.